Fluorescence spectroscopy and multivariate analysis as a greener monitoring tool: characterization of the curing kinetics of bioinspired polymers - Ledesma, Julieta (2015)
The photo-induced curing kinetics of bioinspired copolymers vinylbenzyl thymine (VBT) and vinylphenyl sulfonatewas studied usingfluorescence spectroscopy in combination with multivariate analysis. Fluorescence spectroscopyenables a detailed description of the curing process of VBT copolymers in real time, combining selectivity,simplicity and sensitivity, without the need of sample pre-treatments, being an advantage from the green analyticalchemistry point of view. Two chemometric strategies were used to decompose the data matrix generated whilemonitoring the curing reaction, identifying the evolution of each species involved in the process in conjunctionwith the corresponding pure spectra. A comprehensive comparison between the developed approaches was made,clearly highlighting the advantages and disadvantages of both of them. The use of multivariate analysis applied tofluorescence spectroscopic data to study curing reactions have several advantages such as no sample pre-treatment,no sophisticated equipment requirement, reduced analysis time and use of non-toxic solvents, among others.